'It's made all of us bond since that course…' – a qualitative study of service users' experiences of a CBT anger management group intervention. (5th August 2014) - MacMahon, P.; Stenfert Kroese, B.; Jahoda, A.; Stimpson, A.; Rose, N.; Rose, J.; Townson, J.; Hood, K.; Willner, P.
Abstract Background People with intellectual disabilities (ID) are rarely asked about their experiences as users of psychological services and little is known about the views of clients with ID who have undergone cognitive behavioural therapy (CBT). This study aimed to gather the views of adults with ID who had recently taken part in a cluster randomised control trial (RCT) of a staff‐delivered manualised CBT anger management group intervention. Method A qualitative method, Interpretative Phenomenological Analysis (IPA), was employed and eleven participants were interviewed. The interviews took place after the intervention, within two weeks of the end of the group, to gain an understanding of service users' experiences of participating in a CBT group. Results IPA of the interview transcripts indicated that the intervention was experienced as effective and enjoyable and a number of themes were identified including: 'the importance of relationships', 'a new me', 'new and improved relationships', 'presenting myself in a positive light' and 'what the group didn't change'. Conclusions The results will be discussed in the context of applying group CBT for adults with ID and implications for service development.